2019
DOI: 10.1098/rsos.181133
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control is associated with tobacco and alcohol consumption in young adults of the Avon Longitudinal Study of Parents and Children

Abstract: Individuals appraise events as a consequence of their own actions (i.e. internal locus of control, LoC) or as the outcome of chance or others' will (i.e. external LoC). We hypothesized that having a more external LoC would be associated with higher risk of tobacco and alcohol use. Few studies have examined this association using large prospective data. We evaluated within the Avon Longitudinal Study of Parents and Children (ALSPAC) the associations between LoC at 16 and tobacco and alcohol consumption at 17 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 60 publications
3
25
1
Order By: Relevance
“…Second, to answer research question 2 on the effects of aggression and self-control on maladaptive game use and life satisfaction, the results of this study coincided with those of previous studies, including related studies. Hypothesis 3 states that children's self-control decreases their maladaptive game use [47][48][49][50][51][52][53][54][55][56][57] and increases their life satisfaction [58][59][60][61]. On the contrary, Hypothesis 4 states that children's aggression increases their maladaptive game use [67,[69][70][71][72] and decreases their life satisfaction [74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, to answer research question 2 on the effects of aggression and self-control on maladaptive game use and life satisfaction, the results of this study coincided with those of previous studies, including related studies. Hypothesis 3 states that children's self-control decreases their maladaptive game use [47][48][49][50][51][52][53][54][55][56][57] and increases their life satisfaction [58][59][60][61]. On the contrary, Hypothesis 4 states that children's aggression increases their maladaptive game use [67,[69][70][71][72] and decreases their life satisfaction [74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of problematic behavior such as hyperactivity and delinquency are heavily focused on self-control [46]. Studies demonstrated that high self-control strengthens the prevention of addiction problems such as drugs, alcohol, and smoking [47][48][49][50] and facilitates decision making, emotional control, and impulse resistance related to addiction issues [51,52]. Individuals with high self-control succeed in controlling their desire and determination to commit problematic behavior, whereas individuals with low self-control are more susceptible to problematic behaviors such as violent crimes by failing to overcome their impulses and temptations [53,54].…”
Section: Self-control As a Coping Strategymentioning
confidence: 99%
“…[2931] This social patterning of higher tobacco use amongst individuals of lower socioeconomic position may be related to lower locus of control leading to higher initiation and consumption rates, and lower cessation rates due, at least in part, to lower affordability for tobacco cessation treatment. [32,33] A deeper understanding of this social patterning can help develop targeted tobacco control efforts in India’s resource-constrained health system.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that individuals, who use tobacco feel less in control of their lives, believing that chance/destiny plays a larger role in their health.In addition, the dimension of 'Powerful others' presented no significant difference between the two groups. Beliefs about control over health outcomes are among the most important motivational factors [25,26,27]. This could possibly explain better oral health related behavior among non-tobacco users, they having more internal health locus of control and also the reason for not taking up tobacco habit [26].…”
Section: Discussionmentioning
confidence: 99%